Edukasi Menabung Sejak Dini Sebagai Upaya Meningkatkan Literasi Keuangan Syariah pada Anak Sekolah Dasar - Selci Putri Suriani Siregar; Riyan Pradesyah (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
The implementation of the Independent Community Service Program (KKN) of the University of Muhammadiyah North Sumatra in 2025 was placed at SD Negeri 102028 Sei Parit, located in Sei Rampah District, Serdang Bedagai Regency. This activity aims to instill the habit of saving from an early age in elementary school students as an effort to improve Islamic financial literacy in order to form a character of thrift, responsibility, and financial intelligence. The method used is an interactive learning approach through educational stories, games, learning videos, and mini banking simulations. The results of the activity show that students have a better understanding of the importance of saving, managing pocket money, are able to explain the benefits of saving in their own words, and are encouraged to start saving habits, both at home and at school. Early savings education has proven effective in fostering awareness of wise and future-oriented money management and is expected to become an applicable model for Islamic financial literacy learning at the elementary school level.